Collaborative Governance in Building Utilization Cultural Heritage in Metro City Through the Lens of a Socio-Legal Regime - Denny Sanjaya; Bambang Suhada; Bernard Sipahutar; Andrie W Setiawan (Jambe Law Journal, 2021)
The paradigm of the utilization of cultural heritage is aimed at the welfare of the community. Metro City of Lampung has buildings for cultural heritage from colonization era which are in need with optimum participation of various stakeholders to keep the cultural heritage existence to improve the welfare of the people. The artcle analysis the implementation of collaborative governance in the utilization of cultural heritage buildings in Metro City and ways to encourage strengthening collaboration within the framework of regional regulations in the utilization. Uses a socio-legal approach, it adresses the implementation of collaborative governance offered by Ansel and Gash (2007) with regards to conditions, institutional design, leadership, and collaborative process. Despite a local research in origin, the topic addressed in this article may have wider impact to national level in Indonesia. It is demonstrated that the use of collaborative governance through the concept of gotong-royong (mutual help) has proven to have an impact on the growth of various initiatives and public participation in the development of cultural heritage in Metro City. In addition, to strengthen collaborative governance, the presence of regional regulations related to The Preservation of Cultural Heritage is expected for the process of collaboration among stakeholders.